Realisasi Bentuk Tindak Tutur Direktif Guru Bahasa Indonesia dalam Proses Pembelajaran - Dede Dede; Muhammad Suryadi (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2019)
The purpose of this study was to determine the form of directive speech acts of Indonesian language teachers in the learning process. In this study primary data were collected directly by the researcher in the form of utterances and their context in the Indonesian language learning process that contained directive speech acts. There are three stages in this research, namely the provision of data, data analysis and presentation of data analysis results. The results of the study, in its realization, the use of utterances are still classified as directive utterances even though they are delivered using different modes and are not in accordance with what is said, namely the imperative, declarative, and interrogative modes. The use of command speech is a form of directive speech that is predominantly used by instructors during learning. In conclusion, the directive speech acts of teachers in the Indonesian learning process generally have varied forms, speech containing directive speech tends to be found when the teacher explains the material, and when the teacher gives an assignment. Keywords: Speech Acts, Directive, Indonesian Language Learning